2011
DOI: 10.1093/alcalc/agr024
|View full text |Cite
|
Sign up to set email alerts
|

Alcohol Use Disorders and Hazardous Drinking among Undergraduates at English Universities

Abstract: Undergraduates at some universities in England show very high levels of alcohol-related risk and harm. University authorities should estimate the level of hazardous drinking and alcohol use disorders among students at their institutions and take action to reduce risk and harm accordingly. Research is needed using nationally representative samples to estimate the prevalence of alcohol risk and harm in the UK student population and to determine the future course of drinking problems among students currently affe… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

18
74
3
5

Year Published

2012
2012
2021
2021

Publication Types

Select...
8
1

Relationship

0
9

Authors

Journals

citations
Cited by 86 publications
(100 citation statements)
references
References 36 publications
18
74
3
5
Order By: Relevance
“…While consistent with findings from other countries [40][41][42], the high level of problematic drinking in UK university sportspeople is noteworthy regardless of sponsorship status. The AUDIT total score (mean=14.4) and proportion of hazardous drinkers (84%) in this population group were high compared with estimates of these parameters in a recent study in English university students (mean=9.9, and 61%, respectively) [42].…”
Section: Accepted Articlesupporting
confidence: 83%
“…While consistent with findings from other countries [40][41][42], the high level of problematic drinking in UK university sportspeople is noteworthy regardless of sponsorship status. The AUDIT total score (mean=14.4) and proportion of hazardous drinkers (84%) in this population group were high compared with estimates of these parameters in a recent study in English university students (mean=9.9, and 61%, respectively) [42].…”
Section: Accepted Articlesupporting
confidence: 83%
“…To domnevo lahko potrdi primerjava z nekaterimi drugimi raziskavami med študenti v različnih državah, ki ugotavljajo višjo prevalenco tveganega in škodljivega pitja med študenti v Angliji (61 %), Avstraliji in Novi Zelandiji (42 %), v Španiji (37 %) in na Hrvaškem (43,8 %) (24)(25)(26)(27).…”
Section: Zaključekunclassified
“…Ugotovitev, da je moški spol dejavnik tveganja za tvegano in škodljivo pitje, se sklada z dozdajšnjimi ugotovitvami različnih avtorjev (24)(25)(26)(27). Za študente Univerze v Ljubljani, pri katerih ugotovimo eno izmed oblik tveganega vedenja (na primer kajenje ali izkušnje s prepovedanimi drogami), obstaja večja verjetnost, da so tvegani ali škodljivi pivci.…”
Section: Zaključekunclassified
“…Additionally, it is possible that there is less of a gulf between university culture and university sport culture in England than we might think. For example, Heather et al (2011) found that nearly 61% of students in England drank to at least hazardous levels.…”
Section: Outgoing and Friendly' 'If I'm Drinking It's Easier To Exprmentioning
confidence: 99%